Game addiction: a current review - Doğan Keskin, Ayten; Aral, Neriman (Journal of Dependence, 2021)
Many digital games have emerged with the effect of technological developments in the 21st century. The overuse of these games has brought new diseases along. The most common of these diseases is game addiction. Game addiction is one of the behavioral addictions. Game addiction is defined by features such as being mentally busy with the game, thinking about the game, disrupting daily routines, continuing to play despite having negative consequences in academic, social and family life, reacting when playing is prevented, conflict, and exhibiting withdrawal symptoms. Studies on the definition, diagnosis, prognosis and treatment of this disease in our country are at the beginning level. However, along the Covid-19 pandemic, the time spent especially by children and adolescents for playing has increased, and children and adolescents have started to show signs of addiction. It is predicted that after the pandemic, applications to be made to health facilities related to game addiction will increase. For this reason, the study aimed to examine the definition, symptoms, prognosis, diagnostic criteria, prevalence, gender difference, play time, risk factors, effects on the individual and treatment of game addiction. The feature that distinguishes this study from other studies is that it includes a comprehensive explanation of game addiction and the information that forms the basis of the concept of game addiction. The topics discussed in this study are thought to be important, as they will form the basis of studies on game addiction and provide an understanding of the subject.